Evaluation of the simplicity and completeness on two models (manual and web-based) reporting of the case-based measles surveillance system in Special Region of Yogyakarta (DIY) - Kornelius Langga Son; Andri Setyo Dwi Nugroho; Th. Baning Rahayujati (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose: In order to eliminate measles in 2020, the Health Office of DIY has developed the surveillance system by implementing CBMS into two different models (Manual and Web-Based Reporting) that has the main purpose to increase the performance of CBMS in detecting new cases, reporting data about the spread of measles after conducting massive campaign of measles in 2017. This study aimed to evaluate the simplicity and completeness of the CBMS in both models.Method: Descriptive evaluative study was conducted in DIY from January 2019 to March 2019. A total of thirty-four (n=34) respondents of health offices in 5 districts, 20 public health care offices and 4 hospitals. Samples were defined by using purposive sampling based on the completeness of the report. Data about simplicity was collected by using structure questioners from 34 respondents. While in measuring completeness, due to lack of information in the health offices, we only observed secondary data in primary health care offices and hospitals. Data were analyzed by using stata 13.Results: For the attribute of simplicity, 64.31% of respondents mentioned that the manual reporting form was too complicated. Meanwhile, only 8.82% of respondents considered that web-based reporting was more complicated. For the attribute of completeness, we observed the reporting completeness of 9 variables on both models which completeness of 4 variables in manual reporting including the number of epidemiology (77%), the number of vaccination (73%),  date of specimen collection (89.1%), and final classification (36%) were lower than the target (90%). Compared to web-based reporting, there were only 2 variables including date of specimen collection (79%) and final classification (65) which were lower than the target (90%).Conclusion: The study revealed that CBMS web-based reporting is more simple and complete than CBMS manual reporting. It was clearly seen that completeness in the final classification has the lowest percentage in both models. The system must be simplified, so that lack of reporting completeness on both models can be overcome.